Glocalization and Teacher Education – Ethical Considerations in Challenging Times - Sabrina Viktoria Bacher; Kateryna Binytska; Christian Kraler (Pedagogical Discourse, 2022)
The article emphasizes that global thinking begins at the structural level of educational programs on teacher preparation, and we offer the example of Ukraine, which recently underwent a large-scale reform of its higher education system towards international standardization, which included their educational program on teacher preparation. At the same time, the process of modernization of higher education in Ukraine has a somewhat one-sided focus on the global sphere and neglects some local features, which has led to the emergence of problems.This article explores the connection between glocalization and teacher education from methodological and ethical perspective. We argue that global competence helps teachers and future generations to develop a multi-perspective view to accurately respond to current and future challenges and understand the world in its complexity. This mindset also enables them to make thoughtful ethical decisions based on well-considered global principles. In addition, we argue that glocalization begins at the structural level, and offer the example of Ukraine, which recently underwent a large-scale reform of its education system, including teacher education. However, the reform focused mainly on the global sphere and neglected some local features, leading to numerous problems and challenges.To better understand the idea of glocalization in teacher education from the ethical perspective, future scientific researches can be focused on the study of the international teacher education programs, which find a balance between national traditions and international developments in education, so different systems can learn and enrich each other. Of course, the article does not cover all theoretical aspects of the considered problem and provides further scientific discussions about glocalization in teacher education.